CLINICO-THERAPEUTIC MANAGEMENT OF ACUTE THEILERIOSIS IN A COW CALF - Bhanot, Vandana; Mehla, OP; Deep, Karnal (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
Tropical theileriosis is a disease of global economic importance in cattle, caused by the tick borne protozoan parasite Theileria annulata, and transmitted by ticks of the genus Hyalomma (Brown, 1997; Preston, 2001). The parasite is a serious constraint to cattle poduction in endemic areas, causing lethal infections in exotic cattle and considerable mortality in indigenous as well as crossbred stocks (Forsyth et al., 1997). A case of an acute tropical theileriosis in a 2 months old cow calf was reported and its successful treatment is discussed in present study.